ANÁLISE DO ATENDIMENTO EDUCACIONAL ESPECIALIZADO NO MUNICÍPIO DE SERROLÂNDIA – BAHIA - Silva, Osni Oliveira Noberto da; Ferreira, Márcio dos Santos; Miranda, Theresinha Guimarães; Bordas, Miguel Angel Garcia (Faculdade de Filosofia e Ciências, 2019)
The purpose of this paper was to analyze the Specialized Educational Assistance offered by the municipality of Serrolândia/BA. According to information obtained from the Department of Education in 2018, the ESA has thirty students enrolled and four teachers who make up the teaching staff. Of the thirty students, eighteen are male and twelve female, with ages ranging from 4 to 34 years and 23 of them have medical diagnosis. All the teachers were contacted and accepted to participate in our study, answering a questionnaire with closed questions and multiple choice. Regarding the teachers who work in the ESA, there is a great experience in the area of ??education of all of them, although most of it has been done in regular primary education. Because of the proximity to the current retirement time, it is important that municipal management is already beginning to worry about new professionals who will replace the current teachers in case of retirement. Regarding the physical structure, it is observed that some points still need to be improved, with special attention the physical adaptations of bathroom, ramp etc.